RUSTY HATRED IN SHAKESPEARE’S COMEDY THE MERCHANT OF VENICE - Andri Setiawan; Ahmad Muhid (Jurnal CULTURE (Culture, Language, and Literature Review), 2017)
The comedy genre drama of Shakespeare The Merchant of Venice is interesting to discuss because it contains topics which will give lessons about how to lead life. Hatred for example is a theme which is fascinating to discuss because it occurs in human life. Because of this, the writer decides to analyze it under the title of “Rusty Hatred in Shakespeare’s Comedy The Merchant of Venice”.The writer uses library research to get the main data of the text drama The Merchant of Venice. Secondary data, such as opinions of the experts are taken from various sources like books, webs, internet and so forth. The approach that the writer uses is structural approach because it is an approach that concerns about the elements that build a literary work, like theme, character, setting, plot and so forth.Hatred that the Jewish Shylock possesses is increasing to extreme level. It starts from his being mocked and labelled as a dog until being spitted on cloak and beard that happen many times. Besides that, his business of interest is being constrained because Antonio, a rich Christian merchant, takes no interest of lending his money. This condition makes Shylock hateful, plans to revenge, and kills Antonio carefully.The type of hatred that Shylock has is racial and religious. Shylock hates Antonio because he is a Christian, not a Jew, and vice versa. On the other hand, Antonio also hates Shylock because Shylock is not a local citizen, just a new comer and moreover he is greedy for money by interest. His rusty hatred has made him bepunished by court, acquisition on all his wealth and the obligation to be Christian because he has planned to kill a local Christian Venetian, Antonio.Key words: The Merchant of Venice, hatred, William Shakespeare, racism